Sung Point and Omolokô: art and terreiro culture (Revista Apotheke, 2024)
The article analyzes how the educabilities articulated with sung points in the Ilê de Obaluaê, Umbanda de Omolokô terreiro in Juiz de Fora, MG, can contribute to thinking about art/education based on the community announced by Bastos (2005). Here we defend that educational actions start from the community to combat the coloniality of knowledge, being and power, as operations of subjugation of colonized peoples (WALSH, 2012). When analyzing the aesthetic and artistic dimensions of terreiro communities, we emphasize that such dimensions are inseparable from the experience and rites, represented in the visual organization of sacred artifacts, in the cuisine of the saint, in the ritualistic dances and music. Thus, when working with Afro-Brazilian religions, art/education must necessarily pay attention to everyday life, where all the symbolic load of the community is expressed. This research was not carried out to exhaust a theme, but rather to open paths, establish a position and suggest directions at the crossroads of other possible “arts/educations”.
Keywords: sung points; Umbanda of Omolokô; community-based art/education